2014
DOI: 10.1097/ccm.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Range of Global End-Diastolic Volume for Fluid Management After Aneurysmal Subarachnoid Hemorrhage

Abstract: Our findings suggest that global end-diastolic volume index impacts both delayed cerebral ischemia and pulmonary edema after subarachnoid hemorrhage. Maintaining global end-diastolic volume index slightly above normal levels has promise as a fluid management goal during the treatment of subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Yoneda et al 39 reported that patients with DCI exhibit a decreased GEDI in the early stage of SAH (i.e., Days 3-5). Meanwhile, Tagami et al 35 demonstrated that the mean GEDI is an independent predictor of the occurrence of pulmonary edema, and a GEDI of > 921 ml/m 2 is significantly associated with the development of severe pulmonary edema. In addition, an ELWI of > 10 ml/kg is more accurate for diagnosing pulmonary edema than clinical symptoms or chest radiograph findings.…”
Section: Discussionmentioning
confidence: 99%
“…Yoneda et al 39 reported that patients with DCI exhibit a decreased GEDI in the early stage of SAH (i.e., Days 3-5). Meanwhile, Tagami et al 35 demonstrated that the mean GEDI is an independent predictor of the occurrence of pulmonary edema, and a GEDI of > 921 ml/m 2 is significantly associated with the development of severe pulmonary edema. In addition, an ELWI of > 10 ml/kg is more accurate for diagnosing pulmonary edema than clinical symptoms or chest radiograph findings.…”
Section: Discussionmentioning
confidence: 99%
“…They further asserted that the decision to administer a fluid challenge should reflect the baseline SVV and brain tissue oxygen pressure response to the fluid challenge. Another study demonstrated that mean global end-diastolic volume index (normal range 680–800 ml/m 2 ) was an independent risk factor for the development of DCI (when less than 820 ml/m 2 ) and pulmonary edema (when greater than 921 ml/m 2 ) [4 ▪▪ ]. The authors concluded that global end-diastolic volume index should be maintained slightly above normal during fluid management of patients with SAH.…”
Section: Hemodynamic Managementmentioning
confidence: 99%
“…In their recent study including 204 SAH patients, Yoneda et al [39] showed that the cardiac index measured by transpulmonary thermodilution was significantly lower in patients with poor-grade aSAH and that patients developing DCI had a significantly lower global enddiastolic volume index (GEDI) than patients without these neurological sequelae. The same study group was able to show that the GEDI was an independent risk factor associated with the occurrence of DCI and severe pulmonary edema [40], the Scylla and Charybdis of volume therapy in aSAH. They found a lower threshold of 822 ml/m 2 , slightly above the normal range, correlated with an increased risk of DCI.…”
Section: Subarachnoidal Hemorrhagementioning
confidence: 93%
“…They found a lower threshold of 822 ml/m 2 , slightly above the normal range, correlated with an increased risk of DCI. A GEDI threshold above 921 ml/m 2 was best correlated with the occurrence of severe pulmonary edema in 47 of 180 patients after aSAH [40]. The infusion of crystalloid or colloid infusion to increase the cardiac index and raise GEDI above normal values reduced DCI and improved postoperative functional outcome in poor-grade SAH patients [41].…”
Section: Subarachnoidal Hemorrhagementioning
confidence: 94%